Exploration of Arbuscular Mycorrhizal Fungi from Sugarcane Rhizosphere in Marginal Land - Zahraeni Kumalawati; Sri Muliani; Asmawati Asmawati; Kafrawi Kafrawi; Yunus Musa (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2021)
The exploration of arbuscular mycorrhiza fungi from sugarcane plantation in marginal land in South Sulawesi was carried out to find the source of inoculums showing effective infection. Soil samples were taken from four area with different characteristic of marginal land, namely land with low organic matter content, clay texture, limited irrigation, and undulating land. Mycorrhizae contained in the soil samples were then observed, and the spores obtained were used as the source of isolation by a single spore culture. The mycorrhizal spores were isolated by wet sieving and centrifugation method with 48% sucrose, which were observed under a compound microscope for spore details (100-1000x). Sugarcane root samples were taken to observe mycorrhizal infection in sugarcane root tissue by root staining method. The results of the study showed that the greatest diversity of mycorrhizal genera was found in soil samples of Jambua Block (Glomus, Gigaspora, and Sclerocistis) and AJ-5 Block area (Glomus, Acaulospora, and Sclerocistis). Single-spore isolates obtained were Glomus sp. and Acaulospora sp. Infection test result on four sugarcane varieties commonly grown in Takalar Sugar Factory showed that infectivity of mycorrhizal isolate of Acaulospora sp. was the highest (75%) and significantly different (LSD’test, p 0,05) compared to that of Glomus sp. (66%).